Escala de Actitudes hacia el Trabajo en Equipo: diseño y validez de contenido - Idme Apaza, Leyda Flor (2023)
The content validity of the Attitudes Towards Teamwork (AHTE) scale was designed and analyzed. The items were written from a university competence approach and are distributed in 4 dimensions: Identity, Communication, Regulation and Execution. Theoretical relevance, instrumental relevance, representativeness, mastery, valence, uniqueness and clarity of 104 items were evaluated by expert judgment (n=23). The following content validity indices were used: CVR, CVI, CVC and Aiken’s V. The results show values close to 0.0.0. The results show values close to 0.80 in CVI and values higher than 0.9 in CVC Mean and Aiken’s V Mean, being clarity the property to be improved in 28 items. In conclusion, the AHTE scale has evidence of content validity.